2012
DOI: 10.1111/j.1365-2095.2011.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein levels on growth and nutrient utilization of fringe-lipped carp,Labeo fimbriatus(Bloch) fingerlings

Abstract: Effect of various dietary protein levels on growth and nutrient utilization were studied in fringe‐lipped carp, Labeo fimbriatus fingerlings for 60 days. Five practical diets containing graded protein levels of 200, 250, 300, 350 and 400 g kg−1 with respective digestible protein (DP) contents of 192.4, 244.5, 291.6, 339.4 and 391.4 g kg−1 were evaluated as five treatments, T1, T2, T3, T4 and T5, respectively, in triplicate. Each experimental tank (80‐L) contained eight fingerlings (4.9 ± 0.1 g) and was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
4
9
0
Order By: Relevance
“…Protein is one of the major dietary nutrients affecting growth, survival and yield of fish, by providing essential and non essential amino acids to synthesize body protein and energy for maintenance Jena et al [6]. The development of fish feed is essentially based on the information of nutrients digestibility and its conversation rate.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Protein is one of the major dietary nutrients affecting growth, survival and yield of fish, by providing essential and non essential amino acids to synthesize body protein and energy for maintenance Jena et al [6]. The development of fish feed is essentially based on the information of nutrients digestibility and its conversation rate.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Although, demand for this promising species for aquaculture is growing day by day (Power et al, 2009), study on its optimum nutritional requirement is limited. Jena et al (2012) have reported the optimum dietary protein (DP) requirement of L. fimbriatus as 273.0 g kg -1 . As L. fimbriatus is a herbivorous fish, carbohydrate utilisation seems to be very important.…”
mentioning
confidence: 99%
“…The diets were designated as T 1 (27% CP and 26% CHO), T 2 (23% CP and 31.5% CHO) and T 3 (19% CP and 37% CHO), where CP and CHO indicates crude protein and carbohydrate, respectively. The diet T I was considered as the reference diet, where , the CP level was kept at 27%, being the optimum requirement for this species (Jena et al, 2012) and carbohydrate level was maintained at 26%, being the optimum carbohydrate requirement for carps (Sen et al, 1978;Erafanullah and Jafri, 1995), since no literature is available at present on the carbohydrate requirement for this species. Casein (vitamin free) with 85% CP and gelatin with 90% CP served as the source of protein.…”
mentioning
confidence: 99%
“…The value is also low compared the optimal DP/DE ratio reported for other fish species e.g. : Atlantic salmon 17-18 g MJ -1 (Einen and Roem, 1997); gilthead sea bream 19-23 g MJ -1 (Lupatsch et al, 2003b(Lupatsch et al, , 2001; fringe lipped carp 17.2-17.6 g MJ -1 (Jena et al, 2012). The differences in optimal DP/DE ratios within species and between species might be related to differences in body weight between studies.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the range of dietary DP/DE ratio tested was narrow using 4 to 9 levels and few studies included low DP/ DE ratio (below 18 g/kJ). In some fish species studies, broken line analysis was performed to estimate optimal DP/DE ratio (Akpinar et al, 2012;Booth et al, 2007;Jena et al, 2012). In Nile tilapia, information on low DP/ DE ratios is limited, the estimated range and number of DP/DE ratios are small and no broken line analysis has been applied.…”
Section: Introductionmentioning
confidence: 99%